2020
DOI: 10.1155/2020/8282460
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Meniscus Tears in Adolescent Patients Treated with Platelet-Rich Plasma Intra-articular Injections: 3-Month Clinical Outcome

Abstract: Objectives. Meniscus repair is a challenge for a practitioner, as an injured meniscus can lead to osteoarthritic joint changes with a greatly disabling outcome. Platelet-rich plasma has been regarded as a promising therapy to help induce healing. The purpose of the study is to clinically assess the effectiveness of PRP treatment in adolescents with meniscal lesions. Methods. This retrospective study analyzed 30 patients with meniscal tears, aged 12 to 17 years, who had documented MRI meniscal lesion and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In vitro studies demonstrated the antinociceptive and proliferative properties of PRP, which increased extracellular matrix production and meniscal tissue regeneration [ 50 , 53 ]. Furthermore, PRP improved meniscal cell viability in animal studies, increasing meniscal compressive strength through the overexpression of proteoglycans [ 54 56 ]. The current evidence of PRP augmentation for arthroscopic meniscal repair is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated the antinociceptive and proliferative properties of PRP, which increased extracellular matrix production and meniscal tissue regeneration [ 50 , 53 ]. Furthermore, PRP improved meniscal cell viability in animal studies, increasing meniscal compressive strength through the overexpression of proteoglycans [ 54 56 ]. The current evidence of PRP augmentation for arthroscopic meniscal repair is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of meniscal healing, numerous studies ( 14-16 ) have acknowledged that PRP injections could provide an improved clinical outcome in cases where the conservative approach was unsuccessful. Although encouraging, the existing results encounter the limitations of small study groups, the biased, subjective perception of pain from patients, or lack of post-procedure MRI studies, which could support the clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PRP has become a popular choice for soft tissue repair, for example, in aesthetic medicine ( 13 ). In terms of orthopedics and sports medicine, it has shown promising results on pain relief in both in vivo and in vitro models ( 8 , 14-16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteochondral fractures are an infrequent accompanying injury which can be successfully managed with the Steadman technique [7]. Some patients may benefit from platelet-rich plasma (PRP) injections in order to reduce the pain caused by injury to other structures of the knee such as the meniscus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment usually consists of cast or splint immobilization, resulting in longer rehabilitation periods as well as a recurrence rate of up to 44% [6,8]. Surgical treatment is the next recommended step if conservative management fails to improve the symptoms significantly.…”
Section: Introductionmentioning
confidence: 99%